Politics in the Russia-Ukraine War (2022-2024) - Sahl, Dafiq Febriali; Sulaeman, Ghina Hafiya; Saputri, Amallia Andini (The Republic of Indonesia Defense University, 2025)
The Russia-Ukraine War (2022) is a conflict that can be explained in terms of state behaviour (Russia) to defend itself from threats (NATO) by acting aggressively in accordance with Mearsheimer's theory of Offensive Realism. NATO's desire became the regional political context that drove the decision to invade Ukraine in 2022. The invasion had economic (and war) repercussions with international pressure with economic sanctions, but the war was sustained with capital and natural resources from its supporting coalition of powerful oligarchs and siloviki in Putin's circle and a national economic strategy to mitigate the economic sanctions. In addition to economics, the internal conflict within the military with the Wagner Coup was also an implication of the domestic military politics of the Russia-Ukraine War. Using a literature review, these three contexts are important to analyse the political, military and economic implications of the Russia-Ukraine War (2022).